THE RESEARCH RESULTS OF ACTING LOADS ON THE HYDRAULIC CYLINDERSOF THE CONTROL MECHANISM OF A MIDDLE CLASS MOTOR-GRADER MAIN BLADE - Шевченко, В. О.; Рагулін, В. М. (Academic journal Industrial Machine Building Civil Engineering, 2017)
The research results of studying the loadsacting on hydraulic cylinders of the working equipment control mechanism depending on the parameters of its positioning. Keywords:motor-grader, hydraulic cylinders , loads.